2004
DOI: 10.1074/jbc.m408889200
|View full text |Cite
|
Sign up to set email alerts
|

UDP-glucose Dehydrogenase Plays Multiple Roles in the Biology of the Pathogenic Fungus Cryptococcus neoformans

Abstract: Cryptococcus neoformans is a pathogenic fungus surrounded by an elaborate polysaccharide capsule that is strictly required for its virulence in humans and other mammals. Nearly half of the sugar residues in the capsule are derived from UDP-glucuronic acid or its metabolites. To examine the role of these nucleotide sugars in C. neoformans, the gene encoding UDP-glucose dehydrogenase was disrupted. Mass spectrometry analysis of nucleotide sugar pools showed that the resulting mutant lacked both UDP-glucuronic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 37 publications
4
71
0
Order By: Relevance
“…In CHO cells, like in C. neoformans (43), inactivation of UXS resulted in an increase of cellular UDP-GlcA. In vitro experiments have shown that UGDH, which generates UDP-GlcA from UDP-Glc, is inhibited by UDP-Xyl (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CHO cells, like in C. neoformans (43), inactivation of UXS resulted in an increase of cellular UDP-GlcA. In vitro experiments have shown that UGDH, which generates UDP-GlcA from UDP-Glc, is inhibited by UDP-Xyl (42).…”
Section: Discussionmentioning
confidence: 99%
“…1) is known to be inhibited by UDP-Xyl (42). In Cryptococcus neoformans, the absence of cytosolic UXS results in an drastic increase of the UDP-GlcA concentration due to lack of feedback inhibition of the dehydrogenase by UDP-Xyl (43). To investigate the consequences of reduced UDP-Xyl production in the mammalian cell line where UXS is localized in the ER/Golgi lumen, the composition of the pool of relevant nucleotide sugars was determined in wild-type, XylT2 (pgsA-745), and UXS (pgsI-208) mutants using formic acid extraction and HPLC analyses (39).…”
Section: Pgsi-208 Lacks Both Glycosaminoglycans and Xylosylation Of Omentioning
confidence: 99%
“…Thus, Griffith and colleagues studied the consequences of the UGD1 deletion with C. neoformans var. neoformans and demonstrated using mass spectrometry analysis that the ugd1⌬ strains were complexly devoid of UDP-glucuronic acid (18). As UDP-glucuronic acid is the precursor of UDP-xylose, it was important to differentiate the phenotypes associated with the defect of UDP-xylose alone from those associated with the UDP-glucuronic acid/UDP-xylose double defect.…”
Section: Vol 3 2004mentioning
confidence: 99%
“…The C. neoformans capsule contains a side chain of GlcUA and xylose, both of which are derived from UDP-GlcUA. In mutants lacking UDP-Glc DH activity, capsule production appears to be completely eliminated (29). In Streptococcus agalactiae (group B streptococcus), mutants that fail to make the terminal sialic acid of the type III capsule side chain, due to mutation of either the CMP-sialic acid synthetase or the sialyltransferase, continue to produce an apparently normal capsule, albeit at greatly reduced levels (17,65).…”
mentioning
confidence: 99%
“…Cps2K contains the same strictly conserved active site signature sequence of GGXCXXXD, as well as extensive homology to the signature NAD ϩ -and UDPsugar binding domains, found in other UDP-GlcDHs (14). UDPGlcDHs play critical roles in the formation of many microbial capsules, including those of Streptococcus pyogenes (25,66), Escherichia coli K5 (52), Cryptococcus neoformans (29), and many S. pneumoniae serotypes (57), as well as mammalian polymers such as hyaluronan, chondroitin sulfate, and heparan sulfate. In many of these polymers, GlcUA is part of the backbone structure, and for capsules such as type 3 in S. pneumoniae, mutations affecting the synthesis of UDP-GlcUA have severe effects on polysaccharide production and virulence (22,31,61).…”
mentioning
confidence: 99%